Uninvited : living loved when you feel less than, left out, and lonely - TerKeurst, Lysa (Thomas Nelson, 2016)
New York Times bestselling author Lysa TerKeurst leans into the deeply personal topic of rejection and takes readers on a journey to explore its roots; the lies we believe as a result; and the truth about who God is, who we are, and what it looks like to live loved. --